Evangelii Gaudium & Laudato Si’: Apontamentos sobre o magistério social da Igreja Católica Apostólica Romana no papado de Francisco = Evangelii Gaudium & Laudato Si’: notes about social teaching of the Roman Catholic Church in the papacy of Francis - Cavalcante, Thiago Leandro Vieira (Teocomunicação, 2021)
The article analyzes the Apostolic Exhortation Evangelii Gaudium and the Encyclical Laudato Si’ written by Pope Francis with the purpose of highlighting the main aspects present in these documents related to the social teaching of the Roman Catholic Apostolic Church. Pope Francis remains deeply connected with the Social Doctrine of the Church and he exhorts Christians to a real conversion through action guided by that doctrine. It gives great emphasis to the preferential option for the poor and to the search for social justice to the detriment of mere charity. In addition, specifically in Laudato Si’, it brings to the Church Social Doctrine a perspective of integral ecology that emphasizes the need to care for the common home, passing, among other things, an effective change in the current consumption patterns., , O artigo analisa a exortação apostólica Evangelii Gaudium e a encíclica Laudato Si’ escritas pelo papa Francisco com o propósito de destacar os principais aspectos presentes nesses documentos relacionados ao magistério Social da Igreja Católica Apostólica Romana. Conclui-se que o papa Francisco se mantém profundamente conectado com a doutrina social da Igreja e exorta os cristãos a uma real conversão por meio da ação guiada pela referida doutrina. Dá profundo destaque à opção preferencial pelos pobres e para a busca pela justiça social em detrimento da mera caridade. Além disso, especificamente em Laudato Si’, traz para a doutrina social da Igreja uma perspectiva de ecologia integral que enfatiza a necessidade do cuidado com a casa comum passando, entre outras coisas, por uma efetiva mudança nos padrões atuais de consumo.